THE FORMS OF REALIZATION OF GENRE SPECIFICITY IN THE DRAMATIC PLAY DISCOURSE (BASED ON G. B. SHAW'S PLAY «PYGMALION») - Natalia Leonidovna Moskovskaya; Karina Olegovna Kagramanyan (Вестник Северо-Кавказского федерального университета)
The article deals with the genre specificity of discourse in its correlation with a particular communicative situation. The author focuses attention on the verbal means of realization of genre specificity in the dramatic play discourse and provides examples based on the text of a play.